IDNLearn.com offers a seamless experience for finding and sharing knowledge. Our platform provides prompt, accurate answers from experts ready to assist you with any question you may have.
Sagot :
To find the distance between the points [tex]\((-9, -11)\)[/tex] and [tex]\((13, 3)\)[/tex], you can use the distance formula, which is derived from the Pythagorean theorem. The distance formula between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] in a coordinate plane is given by:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here, the coordinates of the two points are:
- Point 1: [tex]\((-9, -11)\)[/tex], where [tex]\(x_1 = -9\)[/tex] and [tex]\(y_1 = -11\)[/tex]
- Point 2: [tex]\((13, 3)\)[/tex], where [tex]\(x_2 = 13\)[/tex] and [tex]\(y_2 = 3\)[/tex]
Now, substituting these values into the distance formula:
1. Calculate the difference in the x-coordinates:
[tex]\[ x_2 - x_1 = 13 - (-9) = 13 + 9 = 22 \][/tex]
2. Calculate the difference in the y-coordinates:
[tex]\[ y_2 - y_1 = 3 - (-11) = 3 + 11 = 14 \][/tex]
3. Square the differences:
[tex]\[ (x_2 - x_1)^2 = 22^2 = 484 \][/tex]
[tex]\[ (y_2 - y_1)^2 = 14^2 = 196 \][/tex]
4. Add these squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 484 + 196 = 680 \][/tex]
5. Take the square root of the sum to find the distance:
[tex]\[ \text{Distance} = \sqrt{680} \approx 26.076809620810597 \][/tex]
Therefore, the distance between the points [tex]\((-9, -11)\)[/tex] and [tex]\((13, 3)\)[/tex] is approximately [tex]\(26.077\)[/tex]. This can be visualized on a graph by plotting the points and using the distance formula to determine the distance between them.
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
Here, the coordinates of the two points are:
- Point 1: [tex]\((-9, -11)\)[/tex], where [tex]\(x_1 = -9\)[/tex] and [tex]\(y_1 = -11\)[/tex]
- Point 2: [tex]\((13, 3)\)[/tex], where [tex]\(x_2 = 13\)[/tex] and [tex]\(y_2 = 3\)[/tex]
Now, substituting these values into the distance formula:
1. Calculate the difference in the x-coordinates:
[tex]\[ x_2 - x_1 = 13 - (-9) = 13 + 9 = 22 \][/tex]
2. Calculate the difference in the y-coordinates:
[tex]\[ y_2 - y_1 = 3 - (-11) = 3 + 11 = 14 \][/tex]
3. Square the differences:
[tex]\[ (x_2 - x_1)^2 = 22^2 = 484 \][/tex]
[tex]\[ (y_2 - y_1)^2 = 14^2 = 196 \][/tex]
4. Add these squared differences:
[tex]\[ (x_2 - x_1)^2 + (y_2 - y_1)^2 = 484 + 196 = 680 \][/tex]
5. Take the square root of the sum to find the distance:
[tex]\[ \text{Distance} = \sqrt{680} \approx 26.076809620810597 \][/tex]
Therefore, the distance between the points [tex]\((-9, -11)\)[/tex] and [tex]\((13, 3)\)[/tex] is approximately [tex]\(26.077\)[/tex]. This can be visualized on a graph by plotting the points and using the distance formula to determine the distance between them.
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. IDNLearn.com is your reliable source for accurate answers. Thank you for visiting, and we hope to assist you again.